Kesadaran pada Atlet Bola Basket: Pendekatan Psikologis untuk Keterampilan Manajemen Diri pada Atlet Pelajar - Utami, I Gusti Agung Ayu Yunita; Sukartiasih, Wayan; Cendrawati, Kadek Bintang (Neolectura, 2024)
Basketball athletes can improve their performance, manage their stress, and stay mentally balanced by using mindfulness techniques. Mindfulness helps athletes stay focused on the present, reduce distractions, and increase body awareness and mental resilience through techniques such as breathing exercises, meditation, visualization, and reflection. Mindfulness can improve concentration, emotional control, and readiness to deal with competitive pressure, research suggests. Basketball athletes may become more mentally resilient, allowing them to confidently and optimally face challenges on the court, if they practice mindfulness regularly.